Potential of GIS and remote sensing in mapping land degradation: catchment of the Manyame River, Zimbabwe. Issue 3 (23rd February 2023) - Muhoyi, Hardlife; Muhoyi, Edgar
Abstract: The Manyame River Catchment area in Zimbabwe, is experiencing severe land degradation mainly due to legal and illegal land husbandry practices. These practices are negatively impacting on the sustainability of the existing ecosystems. The conditions of land can be inferred using its vegetative cover e.g., Normalised Difference Vegetation Index (NDVI). Quantitative data relating to land degradation based on notable physical features such as gullies, for Manyame River Catchment at landscape scales is poor. This study focused on the distribution and magnitude of land degradation in the Manyame River Catchment area. The study mapped out the contours of human induced land degradation using a residual trend analysis (RESTREND) method. In particular, the study used remote sensed data (NDVI and precipitation time series) to analyse the shifts over period 2000 to 2017. The analysis used R statistical software packages (RESTREND and Kendal) and Geographic Information System (GIS) techniques to quantify the degradation trends. The results indicated extracts of those areas which experienced significant human induced land degradation during the study period. RESTREND effectiveness was assessed using Mann Kendal Test. The results of this study can be used by natural resources practitioners in monitoring, assessing and managing environmental changes using GIS tools. HIGHLIGHTS: The Manyame River Catchment Area (MRCA) is experiencing severe land degradation. Sustainability of the existing ecosystems is impacted by land degradation. The NDVI can infer the vegetative cover of the MRCA. RESTREND mapped human-induced land degradation in the MRCA. GIS and remote sensing techniques quantified the degradation trends in the MRCA. Graphical Abstract